Evolution of University Autonomy and Academic Freedom in the Evaluation of University Faculty Members - I. G. Dezhina (Высшее образование в России)
The article analyzes the changes that have occurred in university autonomy and academic freedom in the late Soviet and post-Soviet period from the point of view of the faculty members of leading universities and the main influencing factors. The aim is to identify successful Soviet practices from the faculty members’ point of view and to assess the possibilities of their use in the current conditions.The study is based on in-depth interviews conducted with faculty members of two leading Russian research universities located in Moscow and Tomsk. The majority of the informants had worked at the universities during the Soviet period. The informants expressed their opinions on the degree of succession  of  university  autonomy  and  academic  freedom  in  their  universities,  and  on  the  factors influencing it.The survey revealed that the Soviet experience is perceived very differently both within and between  universities.  Positive  aspects  of  the  Soviet  experience  include  guaranteed  state  funding  and a well-established system of cooperation with industry based on “economic contracts”. These supported the high status of faculty members. Assessments of the modern period are polar. Some believe that this is the period of a reasonable degree of university autonomy and academic freedom, while others believe that it has been greatly reduced and that state control has increased.Tracing the changes in university autonomy and academic freedom reveals the importance of di-versification, especially in funding schemes. The direct transfer of Soviet practices is hardly possible.